Views on the right to withdraw from randomised controlled trials assessing quality of life after mastectomy and breast reconstruction (QUEST): findings from the QUEST perspectives study (QPS). (March 2014) - Bidad, N.; MacDonald, L.; Winters, ZE.; Edwards, SJL.; Horne, R
The purpose of this study is to examine the importance that real patients attach to their right to withdraw from an on-going feasibility randomised trial (RCT) evaluating types and timings of breast reconstruction (two parallel trials) following mastectomy for breast cancer. Our results show that, while some respondents appreciated that exercising the right to withdraw would defeat the scientific objective of the trial, some patients with a surgical preference consented only given the knowledge they could withdraw if they were not allocated to their preferred treatment.